Visual Laser Ablation of the Prostate (VLAP) - Bird, Doreen; Smith, Susan (Operating Room Nurses Association of Canada Journal, 1995)
Benign Prostatic Hyperplasia is a condition, which occurs commonly in men as they age. The degree of impedence of the ﬂow of urine from the bladder due to prostate gland enlargement varies from a slight slowing of the stream to complete urinary retention. Transurethral Resection of the Prostate (TURP) has historically been the most common treatment of this condition. While other alternative treatments are available, the use of lasers to perform Visual Laser Ablation of the Prostate (VLAP) is moving to the forefront as a treatment of choice for many Urologists.